Heart failure secondary to severe anemia in beta-thalassemia major: a case report - Mathews, Aswathy; Prazad, Amal; Kannan, Bharath Duraisamy Swami; Shanmugam, Dinesh Kumar; Ramamoorthy, Lakshiya (International Journal of Research in Medical Sciences, 2024)
The profile of cardiac involvement in beta-thalassemia major patients in the absence of significant cardiac iron overload is quite rare. This case report focuses on a 3-year-old child with a history of beta-thalassemia who presented with acute heart failure following missed blood transfusions, despite consistent chelation therapy. Clinical evaluation revealed severe anaemia, and cardiac ischemia leading to cardiovascular compromise, despite desirable ferritin levels. The patient’s condition improved with guideline-directed medical therapy, transfusions, and continued chelation. We hypothesize that tissue hypoxia plays a significant role in the development of cardiac ischemia leading to heart failure, highlighting the critical importance of adherence to treatment schedules to prevent severe complications.